Assessing the length of the post-disturbance recovery period for woodland caribou habitat after fire and logging in west-central Manitoba - Metsaranta, Juha M. (Rangifer, 2007)
This study examined the habitat characteristics of areas used by woodland caribou and areas disturbed by fire or logging in the Naosap caribou range in west-central Manitoba. The population inhabiting this area is currently considered to be of high conservation concern. The purpose was to determine how long after disturbance forests again resembled caribou habitat and whether there were differences in the recovery period between fire disturbed and logged areas. Sample transects were located in areas used by caribou and areas disturbed by fire or logging. Previously, it was shown that variables positively associated with habitat suitability in this region were species composition (presence of black spruce), an index of arboreal lichen abundance and tree size, while variables negatively associated with habitat suitability were deadfall abundance and species composition (presence of trembling aspen). It was hypothesized that if disturbed sites had become suitable caribou habitat, then they should be statistically indistinguishable from sites used by caribou based on these variables. Using cluster analysis, it was found that 2 statistical clusters showed the highest level of agreement with sampling clusters, with 88% of plots used by caribou classified into one cluster, and 74% of disturbed plots classified into the other. Although a small proportion (12%) of disturbed plots resembled used plots, 30 years (the age of the oldest disturbed plot) was not enough time, in general, for forest to return to conditions resembling caribou habitat in this region.